Comparison of Posterior Intravaginal Slingplasty with Abdominal Sacrocolpopexy in Severe Uterovaginal or Vault Prolapse: a clinical trial - Zinat Ghanbari; Saphoura Shakoienejad; Mamak Shariat; Nili Mehrdad; Tahereh Eftekhar; Seyed Ali Bashiri (Tehran University of Medical Sciences, 2008)
Objective: The abdominal sacrocolpopexy is the standard method of vaginal prolapse correction and posterior intravaginal slingplasty (PIVS) is a newer procedure with minimal invasiveness. This study compares the effectiveness and complications of these two surgical methods. Materials and Methods: In this non randomized clinical trial study, which was conducted in Imam Khomeini Hospital, Tehran, 51 patients with severe uterovaginal or vaginal vault prolapse were evaluated. From 2001 to 2004 twenty six patients were operated by PIVS method and sacrocolpopexy was performed for the remainders. Data were primarily gathered from patients' folders and further information was achieved by two years follow-up and inviting patients to interview or exam. Results: Eighty percent of women with abdominal sacrocolpopexy were cured compared to 96.2 percent with PIVS. Short-term surgical complications like hemorrhage, perforation, fever and abdominal distention were positive just in 36% of sacrocolpopexy group (p=0.001). Long- term complications like tape or mesh dysfunction were seen in 8% of PIVS group while none of sacrocolpopexy patients presented these complications. Conclusion: According to shorter operating time, lower complications and efficient response to therapy in PIVS method, it can be an alternative procedure for prolapse surgeries. It is preferred in elderly patients with medical problems.